1970
DOI: 10.1159/000224530
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Identification of Sulfated and Non-sulfated Mucopolysaccharides in Regenerating Forelimbs of Adult Urodeles

Abstract: A precise, sequential staining procedure which demonstrates sulfated and non-sulfated mucopolysaccharides and glycogen in the urodele forelimb is described. The process, a combination of the alcian and PAS techniques, has proven valuable in following histogenic events during forelimb regeneration. Non-sulfated mucopolysaccharides are present in apical cap epithelium, sarcoplasm, and bone matrix. Both alcian blue and PAS responses are apparent in dedifferentiating cartilage. Glycogen was apparent in late blaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In the blastema and elongating cone of the newt limb at 10–20 days after amputation, an intense blue staining is seen to reach the apical‐most regions of the blastema, located underneath the wound epidermis (Figures E, F and 5A, B; Schmidt, ; Procaccini and Doyle, ; Alibardi and Sala, ; Mescher and Cox, ). The meshwork of alcianophilic fibrils reaches the basement membrane of the apical wound epidermis, including the apical epidermal cap (Figure A–C).…”
Section: Ha During Limb and Tail Regeneration In Amphibian And Lizardmentioning
confidence: 99%
See 2 more Smart Citations
“…In the blastema and elongating cone of the newt limb at 10–20 days after amputation, an intense blue staining is seen to reach the apical‐most regions of the blastema, located underneath the wound epidermis (Figures E, F and 5A, B; Schmidt, ; Procaccini and Doyle, ; Alibardi and Sala, ; Mescher and Cox, ). The meshwork of alcianophilic fibrils reaches the basement membrane of the apical wound epidermis, including the apical epidermal cap (Figure A–C).…”
Section: Ha During Limb and Tail Regeneration In Amphibian And Lizardmentioning
confidence: 99%
“…In vertebrates, where tail or appendages regeneration occur, in fish and amphibians, the regenerative blastema has a soft consistence due to high hydration and HA content, resembling that of embryonic limb or tail buds. The average content in GAGs in normal and regenerating appendages, largely represented by HA in the blastema (Procaccini and Doyle, ; Toole and Gross, ; Alibardi and Sala, ; Mescher and Munaim, ), is much higher in amphibian tail or limb tissues than in lizard tissues (and in other amniote tissues) (Figure A and B; Alibardi, ). Therefore, in addition to the 80% water limit to organ regeneration, there is also a GAGs limits of 40–45 μg/mg dry weight of GAGs (with HA representing large part of these molecules), under which regeneration is unlikely (Figure B).…”
Section: Appendages Regeneration Occurs In a Hydrated Hyaluronate‐rimentioning
confidence: 99%
See 1 more Smart Citation
“…Serial 10 ¡¿m sections were stained with a combination alcian blue-PAS stain [Procaccini and Doyle, 1970a].…”
Section: Methodsmentioning
confidence: 99%
“…Previous biochemical and a recent transcriptome study have shown that the lizard blastema appears immuno-suppressed in comparison to normal tissues, a condition that likely favors tail regeneration while this is not the case for the limb that instead forms scars (Alibardi, 2014(Alibardi, , 2017bVitulo et al, 2017b). Several mechanisms may be involved, including the immunoregulatory activity of mesenchymal cells (Wang, Ding, & Xu, 2016), but here we have focused on hyaluronate, a large macromolecule produced in high amount during wound healing and blastema formation in amphibians (Contreras et al, 2009;Mescher & Munaim, 1986;Procaccini & Doyle, 1970;Toole, 1997;Toole & Goss, 1971) and lizards (Alibardi, 2014(Alibardi, , 2017bAlibardi & Sala, 1983;Nambiar et al, 2008;Shah & Hiradhar, 1975). In fact, this nonsulfated glycosaminoglycan of high molecular weight (> 500 kDa) has also an immune-suppressive and anti-inflammatory function (Aya & Stern, 2014;Csoka & Stern, 2013;Lee-Sayer et al, 2015;Petrey & de la Motte, 2014;Reiter & Lepperdinger, 2013).…”
Section: Hyaluronate and Appendages Regenerationmentioning
confidence: 99%